2019
DOI: 10.4314/gjds.v16i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the implications of migrant retail trading in Ghana: a stakeholder perspective

Abstract: This study explores the perspectives of relevant stakeholders on the engagement of West African migrants in retail trading businesses meant for indigenes under the Ghana Investment Promotion Centre Act. The study was conducted qualitatively on 13 participants in the Accra Metropolis (Which comprised immigrant key informants and institutional stakeholders) using semi-structured interview guide. Thematic analysis procedure was used to analyse the data and report the findings. The results showed that the immigran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Itinerant immigrant traders are part of the category of migrants whose health-seeking behaviours and practices need to be improved. The term “itinerant trade” is used to describe a livelihood activity that is undertaken outside the authorised standards of business transactions set up by the state (Ghana Statistical Service [GSS], 2012; Yendaw, 2019). Selling food products on the streets or engaging in door-to-door food delivery, including hawking and peddling, are forms of itinerant trading activities (Thorsen, 2012; Yendaw et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Itinerant immigrant traders are part of the category of migrants whose health-seeking behaviours and practices need to be improved. The term “itinerant trade” is used to describe a livelihood activity that is undertaken outside the authorised standards of business transactions set up by the state (Ghana Statistical Service [GSS], 2012; Yendaw, 2019). Selling food products on the streets or engaging in door-to-door food delivery, including hawking and peddling, are forms of itinerant trading activities (Thorsen, 2012; Yendaw et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Accra Metropolitan Assembly (see Figure 1) was chosen as the study locality because it is the most urbanized city in the country with very vibrant immigrant in-flows from neighbouring African states (Ghana Statistical Service, 2012). Thus, Accra Metropolitan Assembly continues to be a major destination for many West African immigrants (Ghana Statistical Service, 2012;Yendaw, 2019). Results from the 2010 Population and Housing Census showed that about 21% of West African immigrants live in the Greater Accra region and Accra Metropolitan Assembly hosts many of these immigrants (Ghana Statistical Service, 2013;2014).…”
Section: Study Locationmentioning
confidence: 99%
“…The term 'itinerant immigrant trader/retailer' has been used in this study to include a wide range of immigrant retailers who transact their retail trades outside the formal arrangements of business operations instituted by the state (Yendaw et al, 2019;Harris, 2009;Hart, 1973). This includes people peddling diverse goods on the streets of major towns; hawkers and peddlers with bicycles, motorbikes, trays, or barrows of wares selling along the streets, selling door to door or from office to office (Yendaw, 2021;Yendaw, 2019;Thorsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I identified these communities during a reconnaissance survey aided by immigrant key informants in the study area. Even though earlier research on this immigrant population abounds in the AMA, the focus has been on their livelihood status (Yendaw, Tanle, & Kumikyereme, 2019a), migration motivations (Yendaw, Borbor, et al, 2019b), and issues on the policy and security implications of their retail trade (Yendaw, 2019). Consequently, information regarding their cross-border migration configurations such as mode of travel and routes of entry are rare.…”
Section: Study Context and Designmentioning
confidence: 99%